1971
DOI: 10.1139/p71-143
|View full text |Cite
|
Sign up to set email alerts
|

Low-Lying Levels of 58Co

Abstract: The odd–odd nucleus 58Co has been investigated experimentally by the 59Co(d,t)58Co and the 55Mn(α,nγ)58Co reactions. In the pickup studies deuteron energies of 15 and 16.5 MeV were used and levels at 0, 25, 52, 112, 365, 375, 456, 888, 1043, and 1078 keV were observed. DWBA analysis showed mixed ln = 1 and 3 transfers for all levels except the last named, which is pure ln = 3. High resolution gamma–gamma coincidence work using the (α,nγ) reaction has revealed the decay properties of a large number of levels up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Table I11 gives excitation energies and their gamma ray decay observed in this experiment. Here also are shown the transitions found by Robertson et al [3] and Zenoulis et al [2] and their intensities.…”
Section: Gamma Ray Spectra and Decayssupporting
confidence: 58%
See 2 more Smart Citations
“…Table I11 gives excitation energies and their gamma ray decay observed in this experiment. Here also are shown the transitions found by Robertson et al [3] and Zenoulis et al [2] and their intensities.…”
Section: Gamma Ray Spectra and Decayssupporting
confidence: 58%
“…The first figure may be too high for reasons mentioned above. Robertson et al[3] have also reported a 684.1 keV transition to the 365 keV level. The ratios of these transitions are 61 : 34 : 5 in agreement with our results.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The projectile-like overlap spectroscopic factors were taken from [63] and the transferred nucleons were bound in Woods-Saxon wells of radius r 0 = 1.25 fm and diffuseness a = 0.65 fm, plus a spin-orbit component of the same geometry with a fixed depth of 6 MeV, the depth of central part being adjusted to give the correct binding energy. The spectroscopic factors and binding potentials for the target-like overlaps were taken from [64,65,66,67].…”
Section: A Cdcc Calculations Ofmentioning
confidence: 99%
“…The 58 Co nucleus has two long-lived isomeric states [1], formed by the parallel and antiparallel coupling of πf 7/2 and νp 3/2 single-particle states [2,3]. The J π = 5 + metastable state decays with a half-life of approximately 9 hours to the 71-day J π = 2 + ground state [4] via a highly converted 25-keV internal transition [5][6][7] of multipolarity M 3 [8,9].…”
Section: Introductionmentioning
confidence: 99%